THE RESEARCH TREND OF INVENTORY MANAGEMENT - Sisca Dian Rahmawati; Marellia Sasa Iswanti; Febrianur Ibnu Fitroh Sukono Putra (Universitas Dian Nuswantoro, 2022)
This study examines inventory management research. This study uses the package (biblioshiny) in the 'R' tool to perform inventory mapping and science analysis by extracting data from Scopus. A total of 4127 research documents were reviewed, including 3562 articles and 565 conference papers. The analysis results show that the development of articles on the theme of inventory management has ups and downs from year to year, so it is considered insignificant. The authors who published the most Inventory Management articles are Cardenas-Barron, LE, Shah, NH, and Taleizadeh, AA. The year with the most inventory management publications was 2007. The highest source is the Journal of Cleaner Production. With 17.6 percent of document publications in 2016, Decision Sciences was the most mentioned subject. The United States has the highest number of published articles. Inventory Control became the primary focus of this topic's research. The study's findings will help businesses gain a better understanding of inventory management. Meanwhile, academic researchers and students can find findings and recommendations for inventory research.Keywords: Inventory; Inventory Management; Bibliometrix Analysis; Inventory Control